2022
DOI: 10.1002/oby.23449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a lifestyle intervention on postpartum weight retention among women with elevated weight

Abstract: Objective: The effectiveness of a pregnancy and postpartum behavioral lifestyle intervention on postpartum weight retention was examined.Methods: Pregnant women with overweight and obesity in South Carolina were recruited into a theory-based randomized controlled trial (n = 112 intervention, n = 107 standard care), which was designed to reduce gestational weight gain and postpartum weight retention.Results: Participants (44% African American, 56% White) had a mean prepregnancy BMI of 32.3 kg/m 2 and were at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The aim of the Health In Pregnancy and Postpartum (HIPP) study, a randomized clinical trial, was to evaluate the impact of a lifestyle intervention (versus standard care) on gestational weight gain (primary outcome) and related outcomes in African American and white women who enter pregnancy living with overweight or obesity [ 13 ]. In earlier papers, we described the study design and methods, including the intervention [ 13 ], as well as recruitment strategies and yields [ 14 ] and the impact of the intervention on gestational weight gain [ 15 ] and postpartum weight retention [ 16 ]. In our two outcome papers [ 15 , 16 ], we reported associations between receipt of counseling calls and gestational weight gain / postpartum weight retention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the Health In Pregnancy and Postpartum (HIPP) study, a randomized clinical trial, was to evaluate the impact of a lifestyle intervention (versus standard care) on gestational weight gain (primary outcome) and related outcomes in African American and white women who enter pregnancy living with overweight or obesity [ 13 ]. In earlier papers, we described the study design and methods, including the intervention [ 13 ], as well as recruitment strategies and yields [ 14 ] and the impact of the intervention on gestational weight gain [ 15 ] and postpartum weight retention [ 16 ]. In our two outcome papers [ 15 , 16 ], we reported associations between receipt of counseling calls and gestational weight gain / postpartum weight retention.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier papers, we described the study design and methods, including the intervention [ 13 ], as well as recruitment strategies and yields [ 14 ] and the impact of the intervention on gestational weight gain [ 15 ] and postpartum weight retention [ 16 ]. In our two outcome papers [ 15 , 16 ], we reported associations between receipt of counseling calls and gestational weight gain / postpartum weight retention. However, these papers did not report other components of intervention delivery overall or with respect to weight-related outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…An additional 5 randomized clinical trials tested interventions extending from pregnancy to postpartum. [72][73][74][75][76] Three of the 5 trials reported significant intervention effects on primary outcomes of body weight. One of the largest trials tested the comparative effectiveness of a health systembased, DPP-derived intervention on 12-month postpartum weight loss in 2280 individuals with gestational diabetes receiving care through Kaiser Permanente Northern California.…”
Section: Postpartum Weight Management Interventionsmentioning
confidence: 99%
“…At 32 weeks, 191 participants (87%) completed the measurement visit; all completed the dietary and HRQOL measures, but 22 did not wear the SenseWear armband. Study adverse events during pregnancy (n=24; 11 behavioral intervention, 13 standard care) are reported elsewhere [35], with all determined to be unrelated to the intervention.…”
Section: Samplementioning
confidence: 99%